P79 Incidence of brain metastases at diagnosis in otherwise stage I non-small cell lung cancer. (12th November 2019) - Farne, HA; Banks, T; Bloch, SA; Ross, CL
Abstract : Introduction: Recently updated NICE guidelines advise against offering 'brain imaging to people with clinical stage I non-small cell lung cancer (NSCLC) who have no neurological symptoms and are having treatment with curative intent'. 1 The rationale given is low prevalence of asymptomatic brain metastases in this group, quoting a prevalence of 4%, with brain imaging delaying potentially curative treatment and incurring additional costs. Proponents of brain imaging argue that the presence of brain metastases significantly changes the treatment plan and thus 4% feels uncomfortably high. There is little data on the incidence of brain metastases at diagnosis in otherwise stage I disease. We have historically performed brain imaging at diagnosis on all stage I patients potentially suitable for radical treatment. In this review of our practice, we sought to assess the impact of the proposed changes in our population. Methods: We identified patients with stage I disease, and stage I revised to stage IV disease solely on the basis of brain metastases (i.e. N0 M1b), from a prospectively gathered database of patients diagnosed with lung cancer in our trust between 1st Jan 2014 and 30th April 2019. For the latter group, we looked for neurological symptoms at diagnosis in case notes. We additionally reviewed the case notes to confirm the histology and, where the staging had been changed in the database, we re-reviewed the relevant investigations. Results: 313 patients had stage I NSCLC and 6 had stage IV NSCLC on the basis of isolated brain metastases, all with neurological symptoms, giving a prevalence of 1.9% (6/313). Excluding those without histological confirmation (suggesting they would not be candidates for radical therapy) gave a prevalence of 1.1% (3/264). No asymptomatic patients (0%) were found to have brain metastases at diagnosis. Conclusions: The prevalence of in our population was lower than that quoted by NICE and supports the guidance that in stage I NSCLC, presenting without neurological symptoms, the benefits of routine bran imaging are too low to justify the cost. Reference: National Institute for Health and Care Excellence. ( 2019). Lung cancer : diagnosis and management (NICE guideline NG122). Retrieved from https://www.nice.org.uk/guidance/ng122